2016
DOI: 10.1021/acs.inorgchem.6b00163
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-dependent SCO Behavior of Dinuclear Iron(II) Complexes with a 1,3,4-Thiadiazole Bridging Ligand

Abstract: Two dinuclear iron(II) complexes [Fe2(μ-L)2]X4*4DMF (X = BF4(-) (1·4DMF) and ClO4(-) (2·4DMF)) with a 1,3,4-thiadiazole bridging ligand have been synthesized and show a very distinct solvent-depending SCO behavior. The complexes represent new solvatomorphs of the first dinuclear iron(II) complexes with the ligand L (2,5-bis[(2-pyridylmethyl)amino]methyl-1,3,4-thiadiazole). The incorporated lattice DMF molecules directly affect the spin state of these complexes. This behavior reveals a structural insight into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 50 publications
(87 reference statements)
1
31
0
Order By: Relevance
“…15b and Table 6). 89 The Rentschler group further investigated the effect of changing the non-coordinated-heteroatom in the five-membered ring, this time to an oxygen atom, generating the oxadiazole analogue, 2,5-bis{[(2-pyridylmethyl)amino]-methyl}-1,3,4-oxadiazole (PMOD, Chart 4). The more electronegative oxygen (cf.…”
Section: Dinuclear Fe 2 L 2 : Pmrt and Related Ligandsmentioning
confidence: 99%
“…15b and Table 6). 89 The Rentschler group further investigated the effect of changing the non-coordinated-heteroatom in the five-membered ring, this time to an oxygen atom, generating the oxadiazole analogue, 2,5-bis{[(2-pyridylmethyl)amino]-methyl}-1,3,4-oxadiazole (PMOD, Chart 4). The more electronegative oxygen (cf.…”
Section: Dinuclear Fe 2 L 2 : Pmrt and Related Ligandsmentioning
confidence: 99%
“…[46][47][48] 11 and in the five new ligands presented in this work (right, violet box), L 2NHIm-meta , L 4NHIm-meta , L 4NMeIm-meta , L 4OIm-meta and L 4SIm-meta . Such ligands have included (Figure 2): mono-and bis-dentate Rdpt, 48 bis-terdentate PMRT/PSRT 11,[49][50][51] and the related PMTD/PMOD [52][53][54] or TMTD 55 all of which have been reported in the literature to form SCO active Fe(II) complexes. Recently, we reported that our general synthetic strategy for accessing Rdpt ligands 38,56 could be extended to access the first examples of ditopic azine-triazole analogues 57 and of azole-triazole monotopic Rat ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive and varied effects that solvent(s) of crystallisation have on the properties of SCO materials is a prime example of this [12,13]. Thus, it has been extensively shown that the spin-transition can be significantly affected by the intermolecular interactions induced by solvent molecules [14][15][16][17][18][19][20][21][22][23][24][25][26]. Solvent molecules of crystallisation can affect the transition temperature (T 1/2 ) [26][27][28][29][30][31][32][33][34][35][36], the nature of the spin-transition as well as the degree of cooperativity and thermal hysteresis that occurs [12,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In some examples, solvent effects can even be reversibly triggered by desolvation and resolvation of the solid material [47][48][49][50]. The onset of an apparent hysteresis, in which irreversible changes in the profile are observed, are often induced by the loss of solvent molecules, a process that tends to stabilise the high-spin (HS) state [24,25,[51][52][53]. As a result, there is potential for thermally induced spin-transitions to be 'tuned' by the adsorption and desorption of solvent molecules of crystallisation, leading to a potential application as chemosensors [20,50].…”
Section: Introductionmentioning
confidence: 99%